PENGARUH KUALITAS DAN KEAMANAN DIGITAL SERVICE TERHADAP KEPUASAN NASABAH PADA BNI SYARIAH KANTOR CABANG JAKARTA BARAT - Vianti Anggun Komala; Nur Melinda Lestari (Prosiding Seminar Nasional Berseri, 2020)
The purpose of this study is to find out the influence between Digital Service Quality, and Digital Service Safety Towards Customer Satisfaction. This type of research uses a quantitative approach. This study took 100 samples from customers who used E-Banking services At BNI Syariah Branch Office in West Jakarta, using the simple random sampling method. As for the method of data analysis using multiple regression analysis models and for data processing using the SPSS 21 program. This research was conducted at BNI Syariah West Jakarta Branch Office. The results of the analysis with a significance level of 5% indicate that between the quality of digital service has a positive and significant effect on customer satisfaction with a level of sig 0.001 <sig 0.05, Digital service security has a positive and significant effect on customer satisfaction with a level of sig 0,000 <sig 0,05. Together the Digital Quality and Safety Service variables a positive and significant effect on customer satisfaction with an F count of 127,194 and a significance level of 0,000 (less than 0.05) with r2 72.4%.